(untitled) (Applied Biological Research, 2023)
The present study was carried out to assess the macro-invertebrate diversity in Patna stretch of river Ganga at four sites during 2017-18. Considering fluctuations in river hydrology after rainy season, the study was conducted twici.ein summer and late winter. A total 1523 organisms belonging to 11 orders and 43 families were recorded. The operculate members of Gastropoda were found dominating in summer season at all the sampling sites and almost identical values of Shannon-Wiener index in river indicated stabilized ecosystem with moderate level of decomposable organic matter. Occurrence of pollution-sensitive Ephemeroptera families and good quantityodissolved oxygen at two upstream sites i.e. Digha Ghat and Gandhi Ghat in winter indicated comparatively good biological water quality of river in this stretch. Presence of families like Corixidae and Nephthyidae indicated moderate level of organic matter decay at Malsalami and abundance of Chironomidae larvae at Fatuha reflected the impact of wastewater discharge into the river. Gradual decrease in Shannon-Wiener diversity index supported the impact opollution at these two downstream sites of Patna stretch of river Ganga.